Review of Statistical Innovations in Trials Supporting Vaccine Clinical Development. (2nd January 2016) - Heyse, Joseph; Chan, Ivan
Abstract : Vaccines have a long history of providing protection to human health. As an example, eradication of the deadly disease, smallpox, was accomplished in 1980 via massive vaccination programs around the world. Vaccination was, in fact, recognized as the greatest public health achievement of the 20th century by the U.S. Centers for Disease Control and Prevention. In recent years, statisticians have played an increasingly important role as collaborative researchers in vaccine development. This review article highlights some of the innovative applications of statistical techniques that have contributed to the successful development of several vaccines for preventing diseases such as chickenpox, herpes zoster, rotavirus gastroenteritis, and cervical cancer. Real life examples will be used to illustrate statistical innovations in several areas, including trial design and adaptation, safety monitoring, endpoint measure, and the evaluation of correlates of protection. Many of these methods, while innovative and novel at the time, are now broadly applied across pharmaceutical and vaccine clinical programs. These statistical contributions are a reflection of the statisticians' engagement and leadership, which has resulted in a substantial improvement of the scientific rigor, quality, and operational efficiency in vaccine development. This article was contributed as part of the 175th Anniversary celebration of the American Statistical Association.